Length-Weight Relationship and Condition Factors of Tenualosailisha During Spawning Season in Labuhanbatu Estuary - Ariani, Fristi; Machrizal, Rusdi; Harahap, Ilham Hakiki (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
The main objective of the study on Tenualosa ilisha was to analyze the length-weight relationship and condition factors of this species during the peak spawning period in the Bilah Rivers, located in Labuhanbatu Regency, North Sumatra. The study was conducted during the peak spawning period of Tenualosa ilisha, which was recorded to occur from February to April at two main sites Bilah River. The study used exploratory methods, which involved visual and physical observations of fish and their environment. The analysis conducted was the biological aspects of the fish length-weight relationship using the linear allometric model (LAM), while the ecological aspects measured were condition factors using the K Fulton equation and the relative weight equation (Wr). The results of the study the coefficient value (b) was determined to be 1.3181 for males and 1.4617 for females, the value of the condition factor for males (K) was 1.372, and for females (K) 1.474, the value of the relative weight (Wr) for males 100.128 and females 1.474 indicates that the growth of fish length is faster than the weight of fish. Analysis of the condition factor shows that the river environment is still in good condition to support the life of Tenualosa ilisha.